Effectiveness of the Teams Games Tournament (TGT) Cooperative Learning Method towards the Arabic Language Learning Achievement of Students at SMP Muhammadiyah 2 Kalasan - Wati, Ana Taqwa; Wahyuni, Sri (Universitas Muhammadiyah Yogyakarta, 2023)
This study utilizes the cooperative learning strategy known as Teams Games Tournament (TGT) along with crossword puzzle games to enhance Arabic language acquisition at SMP Muhammadiyah 2 Kalasan. This study aimed to assess the efficacy of implementing the cooperative teams games tournament approach in enhancing students' academic performance. The research methodology employed is quantitative with a nonequivalent control group design. The study sampled two classes: experimental class 8e and control class 8d. The study employed a census sample, encompassing all pupils in each class, totaling 35 students. Data were gathered using observation techniques, interviews, and Pre Post Test assessments. The data collected using SPSS version 25 indicates that the independent sample t-test yielded a two-tailed significance value of 0.000, which is less than 0.05. Therefore, the null hypothesis (H0) is rejected, and the alternative hypothesis (Ha) is accepted. There is a considerable difference in average student learning achievement between using Teams Games Tournament cooperative learning and not using it. This method of learning facilitates quicker comprehension for pupils by engaging them in educational games relevant to the study topic.